ETIOLOGY, TREATMENT AND SHORT TERM OUTCOME OF VENTRICULAR ARRHYTHMIAS IN PATIENTS ADMITTED TO A TERTIARY CARE HOSPITAL - Zeb, Shah; Adil, Mohammad; Zeb, Junaid; Zeb, Rifaq; Jan, Hikmatullah; Irfan, Mohammad (Journal of Postgraduate Medical Institute, 2017)
Objective: To determine the frequency of various types of ventricular arrhythmias, its causes, treatment, in-hospital course and short term outcome of ventricular arrhythmias in patients admitted to a tertiary care hospital. Methodology: This observational study was conducted in Cardiology Unit of Lady Reading Hospital, Peshawar from Ist September 2014 to 31st March 2015. All patients with ventricular arrhythmias admitted during study duration were included after fulfilling the inclusion and exclusion criteria. Their baseline, clinical, echocardiographic characteristics, treatment and hospital outcome were recorded in a specially designed proforma. SPSS version 19 was used for statistical analysis. Results: A total of 127 patients were included in the study. Males were 93 (73.22%). Mean age was 43.42 ±10.7 years. Causes of ventricular arrhythmias were acute coronary syndrome 51 (40.15%), ischemic cardiomyopathy 27 (21.25%) and idiopathic dilated cardiomyopathy 13 (10.23%). Successful pharmacological cardioversion was achieved in 29 (22.83%) patients with amiodarone and 3(2.36%) patients with lignocaine. The rest of patients were cardioverted with electrical cardioversion. A total of 8 (6.3%) patients expired. Conclusion: Most common cause of ventricular arrhythmias was coronary artery disease followed by ischemic and dilated cardiomyopathies. Commonly used technique of cardioversion was pharmacological for hemodynamically stable patients and electrical for hemodynamically unstable patients.